Comparison of electromagnetic navigation-guided and conventional blind nasojejunal tube placement in mechanically ventilated patients: a prospective non-randomized controlled study with two stages - Yuan, You; Fu, Jing; Wang, Benjing; Zhong, Mingli; Luo, Xi; Wang, Yuqiang; Luo, Qian; Zhang, Xia; Hu, Rujun (Frontiers in Nutrition, 2026)
BackgroundDuring enteral nutrition support for mechanically ventilated patients, nasojejunal tube (NJT) placement encounters significant challenges in operational efficiency due to the lack of highly effective bedside techniques. Compared to the conventional blind insertion method for NJT placement (CBN-P), the electromagnetic navigation-guided placement technique (ENG-P) potentially offers superior advantages in terms of safety, procedural efficacy, cost-effectiveness, and the timeliness of clinical decision-making. However, the existing body of research in this area remains limited.ObjectiveThe study aimed to evaluate and compare the clinical efficacy of ENG-P vs. CBN-P in mechanically ventilated patients.MethodsThis was a prospective, non-randomized, two-phase cohort study. Patients requiring NJT placement were divided into control (CBN-P) and intervention (ENG-P) groups, enrolled from December 2024 to February 2025 and April to June 2025, respectively. Primary and secondary outcomes included first-attempt success rate, procedure duration, reinsertion frequency, patient discomfort, operator satisfaction, economic costs, clinical decision-making efficiency, and complication rates.ResultsThe ENG-P cohort demonstrated statistically superior performance compared to the CBN-P group, with significantly higher first-attempt success rates (81.36% vs. 65.85%, P = 0.042), shorter procedure duration (median 18 vs. 20 min, P < 0.001), and fewer re-insertion attempts (median 0 vs. 1, P = 0.001). No significant intergroup differences were found in patient discomfort, as measured by CPOT scores (P = 0.074), or in overall procedural success rates (84.75% vs. 78.05%, P = 0.253). The ENG-P technique showed notable improvements in several parameters: increased operator satisfaction (median score 8 vs. 6, P < 0.001), fewer radiographic confirmations required (P = 0.004), lower procedural costs (P = 0.005), and higher jejunal placement accuracy (81.36% vs. 40.24%, P < 0.001). In terms of clinical decision-making efficiency, the ENG-P group had a significantly shorter time from decision to enteral nutrition initiation (median 9.0 vs. 11.0 h, P = 0.001). However, no significant differences were observed in decision-to-placement time or decision-to-first radiographic confirmation time (both P > 0.05). Complication rates, including mucosal injury, coughing reflex, and tube obstruction, were similar between the two groups (all P > 0.05).ConclusionENG-P technique offers significant advantages over CBN-P, including higher first-attempt success rates, shorter procedure durations, fewer reinsertions, and lower healthcare costs. Additionally, it enables earlier enteral nutrition initiation while maintaining a favorable safety profile, making it the optimal choice for bedside NJT placement in ICU settings.Clinical trial registrationhttp://www.chictr.org.cn, identifier ChiCTR2500108091.